Synthesis of V2O5/Single-Walled Carbon Nanotubes Integrated into Nanostructured Composites as Cathode Materials in High Performance Lithium-Ion Batteries - Nojan Aliahmad; Pias Kumar Biswas; Hamid Dalir; Mangilal Agarwal (Energies, 2022)
Vanadium pentoxide (V2O5)-anchored single-walled carbon nanotube (SWCNT) composites have been developed through a simple sol–gel process, followed by hydrothermal treatment. The resulting material is suitable for use in flexible ultra-high capacity electrode applications for lithium-ion batteries. The unique combination of V2O5 with 0.2 wt.% of SWCNT offers a highly conductive three-dimensional network. This ultimately alleviates the low lithium-ion intercalation seen in V2O5 itself and facilitates vanadium redox reactions. The integration of SWCNTs into the layered structure of V2O5 leads to a high specific capacity of 390 mAhg−1 at 0.1 C between 1.8 to 3.8 V, which is close to the theoretical capacity of V2O5 (443 mAhg−1). In recent research, most of the V2O5 with carbonaceous materials shows higher specific capacity but limited cyclability and poor rate capability. In this work, good cyclability with only 0.3% per cycle degradation during 200 cycles and enhanced rate capability of 178 mAhg−1 at 10 C have been achieved. The excellent electrochemical kinetics during lithiation/delithiation is attributed to the chemical interaction of SWCNTs entrapped between layers of the V2O5 nanostructured network. Proper dispersion of SWCNTs into the V2O5 structure, and its resulting effects, have been validated by SEM, TEM, XPS, XRD, and electrical resistivity measurements. This innovative hybrid material offers a new direction for the large-scale production of high-performance cathode materials for advanced flexible and structural battery applications.